Popular Culture And Local Wisdom: A Semiotic Analysis of “Lathi” and “Wonderland Indonesia” Songs - Budiman, Kurniawan Agus Fiqih (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. Music, as the name suggests, is a cultural product that intersects with human creativity in the realm of entertainment industry. As popular culture and local wisdom collide, music can better portray a particular indigenous society’s characteristics due to the amalgamation of current trends and sacred local values. This study aims to examine the songs of “Lathi” and “Wonderland Indonesia,” interpreting the implicit meanings of any semiotic symbols they contain. The data were obtained from the songs’ music videos published on their official YouTube channels and credible journal articles, utilizing a qualitative-descriptive method and semiotic theory by Roland Barthes. In order to accentuate clarity, this study broke down and mapped out three (3) notable processes such as data collection, data analysis, and data interpretation. The result shows that both “Lathi” and “Wonderland Indonesia” songs’ semiotic signs tend to integrate Indonesian traditional culture with western popular culture. Some evidence include the Indonesian traditional arts (gamelan, wayang kulit, stuffed horse, etc.) and Electronic Dance Music (EDM). In a global context, the songs are intended to embody acculturation between two exceptionally distinct cultures. Despite the widespread of popular culture phenomenon, Indonesians stay committed to upholding nationalism and local wisdom. Let alone the global citizens are more likely to be exposed to Indonesian traditional culture. Keywords: Popular Culture, Local Wisdom, Semiotic, Music, Electronic Dance Music (EDM)